Gold and South Africa's Great Depression. Issue 2 (4th May 2021) - Eichengreen, Barry
ABSTRACT: In this paper I seek to understand the roots of South African macroeconomic outperformance since 1929 and whether it can be reconciled with what I have described as conventional wisdom about recovery from the Depression. Unsurprisingly, I find a way of fitting South Africa into that story. In addition, I try to understand better why, if going off the gold standard was so beneficial, indeed even more beneficial for South Africa than for other countries, it was so strongly resisted.